(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background: Atopic dermatitis (AD) is a chronic inflammatory disease of the skin that occurs in persons of all ages but is more common in children. Objective: To determine the effect of breast feeding on atopic dermatitis. Methods: A descriptive study carried on pediatric patients visiting asthma and allergy center and pediatrics out patient in Tikrit Teaching Hospital from March 2007 to August 2007. This study included 100 patients with AD; 58 cases (58%) were males and 42 cases (42%) were females, they all underwent full history, clinical examination and blood sampling for total WBC count, eosinophil cells count, and total serum IgE. Results: Statistical analysis was done by using (ANOVA, Chi-square test). There was significant association between severity of AD according to scorad index (S.I) and type of infant feeding, the mean severity score (S.S) for the breast fed (B.F) children was 21.48±4.96, while the mean S.S for the formula fed (F.F) children was 35.70±9.79, p value ? 0.05. There was a significant association between the hematological parameters of disease activity (total serum IgE level, eosinophil count) and type of infants feeding; the mean total serum IgE level for the B.F children was 211±178.7 IU/ml, was lower than mean total serum IgE level for F.F children (638.2±355.8 IU/ml). The mean eosinophil cells count for the B.F children (355.7±193.1) cell/?l was lower than the mean eosinophil cells count for the F.F children (654.8±236.3) cell/?l. Conclusions: There is significant association between the type of feeding and the level of hematological parameters (IgE and eosinophil count), and that breast feeding is protective against development of severe AD. Key words: atopic dermatitis, breast feeding, IgE, eosinophil